Microstructure and mechanical behavior of AA6082-T6/SiC/B4C-based aluminum hybrid composites. (17th February 2018) - Singh, Gurpreet; Goyal, Sanjeev
ABSTRACT: The microstructural and mechanical behavior of hybrid metal matrix composite based on aluminum alloy 6082-T6 reinforced with silicon carbide (SiC) and boron carbide (B4 C) particles was investigated. For this purpose, the hybrid composites were fabricated using conventional stir casting process by varying weight percentages of 5, 10, 15, and 20 wt% of (SiC + B4 C) mixture. Dispersion of the reinforced particles was studied with x-ray diffraction and scanning electron microscopy analyses. Mechanical properties such as micro-hardness, impact strength, ultimate tensile strength, percentage elongation, density, and porosity were investigated on hybrid composites at room temperature. The results revealed that the increase in weight percentage of (SiC + B4 C) mixture gives superior hardness and tensile strength with slight decrease in percentage elongation. However, some reduction in both hardness and tensile strength was observed in hybrid composites with 20 wt% of (SiC + B4 C) mixture. As compared to the un-reinforced alloy, the improvement in hardness and tensile strength for hybrid composites was found to be 10% and 21%, respectively. Reduction in impact strength and density with increase in porosity was also reported with the addition of reinforcement.